Factors affecting current account in the Republic of Macedonia - Makrevska disoska, Elena; Trpkova nestorovska, Marija (Center of Economic Analysis- CEA, 2015)
Large and persistent current account deficit in most of the transition countries have attracted considerable attention, especially with the beginning of the world economic crisis. Even though common trends in the transition countries are included in the analysis, the main focus of this paper is to provide theoretical and empirical study of the main determinants of the current account in Macedonia. Multiple regression model with ordinary least squares estimator (OLS) was used for the analyzed period January 2003 – September 2012. According to the results, the variables: budget deficit, foreign direct investments, ratio of export and import, new approved credits are statistically significant determinants of the current account in Macedonia. In general, these are structural factors that affect the external imbalance. Still, part of the deepening of current account deficit (especially during third quarter of 2007 and first quarter of 2009) appears to be related to external shocks: global increase of the prices and world economic crisis. These cyclical factors reversed alongside the economic recovery during 2009, and the current account deficit was back to its average levels. This indicates the urgent need for structural changes in the Macedonian economy in order to decrease its external vulnerability in the future.
Keywords: Current account; external imbalance; trade; foreign direct investments